Neutrino flavor-mass uncertainty relations and an entanglement-assisted determination of the PMNS matrix - Flörchinger, Stefan; Schwindt, Jan-Markus (Arxiv, 2018)
As a result of a non-trivial mixing matrix, neutrinos cannot be simultaneously in a flavor and mass eigenstate. We formulate and discuss information entropic relations that quantify the associated quantum uncertainty. We also formulate a protocol to determine the Pontecorvo-Maki-Nakagawa-Sakata (PMNS) matrix from quantum manipulations and measurements on an entangled lepton-neutrino pair. The entangled state features neutrino oscillations in a conditional probability involving measurements on the lepton and the neutrino. They can be switched off by choosing a specific observable on the lepton side which is determined by the PMNS matrix. The parameters of the latter, including the CP-violating phase $δ$, can be obtained by guessing them and improving the guess by minimizing the remaining oscillations.
Gesehen am 16.01.2019